1995
DOI: 10.5254/1.3538731
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Properties of Rubber-Carbon Black and Carbon Black-Oil Compounds Including Measurements at Very Low Shear Stresses

Abstract: The rheological properties of binary rubber-carbon black compounds at compositions 5, 20, 30, 40 and 50 volume percent carbon black have been investigated as well as ternary compounds with rubber/carbon black/oil compositions of 70/20/10, 60/20/20 and 50/20/30, respectively. The compounds were investigated using (1) a constant stress creep instrument at very low rates of deformation, (2) a rotational rheometer at intermediate shear rates and (3) a capillary extrusion instrument at higher shear rates. In experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Figures 10 and 11 for the talc-filled compound system and Figures 12 and 13 for the calcite-filled system showed that shear viscosity increases with increasing the particle loadings, and the shear viscosity increases with decreasing the shear rate, as noted by various other studies on PS-CaCO 3 compounds. 5,7 As the shear stress decreases to very low levels, the shear viscosity was found to exhibit a plateau, as had been previously observed in our laboratories by Osanaiye et al 31 and Araki and White. 32 At still lower shear stresses, many of the compounds exhibit yield stresses.…”
Section: X-ray Orientation Measurementssupporting
confidence: 83%
See 2 more Smart Citations
“…Figures 10 and 11 for the talc-filled compound system and Figures 12 and 13 for the calcite-filled system showed that shear viscosity increases with increasing the particle loadings, and the shear viscosity increases with decreasing the shear rate, as noted by various other studies on PS-CaCO 3 compounds. 5,7 As the shear stress decreases to very low levels, the shear viscosity was found to exhibit a plateau, as had been previously observed in our laboratories by Osanaiye et al 31 and Araki and White. 32 At still lower shear stresses, many of the compounds exhibit yield stresses.…”
Section: X-ray Orientation Measurementssupporting
confidence: 83%
“…33 They used creep measurements. Apparent yield values significantly overestimated true values, as pointed out by Osanaiye et al 31 They carried out creep experiments of a carbon black-filled ethylene-propylene terpolymer (EPDM) at 100°C using sandwich viscometer at very low shear stress. The talc particle-filled system exhibits higher yield values compared to the calcitefilled system.…”
Section: Shear Viscositymentioning
confidence: 96%
See 1 more Smart Citation
“…This is associated with significant changes in the rheological properties, particularly with a yield behavior well documented for highly filled elastomers in earlier works (e.g., ref. 6). In this study, we focused on the fluidlike behavior of elastomer compounds, selecting carbon black volume fractions below 0.15 so that no yield behavior would be expected.…”
Section: Materials Preparationmentioning
confidence: 99%
“…It was primarily used in the creep mode. Weight compensation of the inner member (22,23) was considered but was not used a t 180°C. The shear stresses were calculated from…”
Section: Rheological Measurementsmentioning
confidence: 99%